EVALUATION OF EDUCATION AND TRAINING PROGRAM LEADERSHIP LEVEL IV STATE CIVIL SERVANTS OF NAVY - Sri Nurhayati; Adi Bandono; Bambang Suharjo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
To create the human resources of the apparatus that possesses these competencies, it is necessary to improve the quality of professionalism and develop the insight of Civil Servants. One effort to improve the quality of professionalism and the development of insights of Civil Servants is through the Education and Training program. Evaluation of Education and Leadership Training Level IV as one type of employee development is carried out to achieve the Echelon IV Position competency requirements and achievement of performance improvement in accordance with the main tasks and functions as well as authorities in each work unit.is conducted to evaluate: (1) the basis and objectives of Level IV Leadership Education and Training, as well as the feasibility of the organizing agency, (2) clarity of the characteristics of Education and Training participants, the state of the lecturers, curriculum, facilities and infrastructure, (3 ) compliance with the curriculum and program schedule (4) overall assessment of participants, lecturers and organizers. The approach used in this study is a program evaluation approach using the CIPP model (Contex, Input, Process, Product). The results obtained by the evaluation of Contex namely the foundation of the program in accordance with applicable laws, the purpose of this program is suitable to improve the competence of Echelon IV, while the evaluation of Input shows participants meet the criteria, but the lecturer is still very limited and the curriculum has referred to the guidelines, facilities that meet the standards appropriateness. Process component evaluation program compliance with curriculum and schedule meets the criteria, Product component evaluation of the overall results of participants, lecturers and organizers meet the criteria.Keywords:Program Evaluation, CIPP Model, Education and Leadership Training Level IV.